Using Geographic Information Systems and the Analytical Hierarchy Process for Delineating Erosion-Induced Land Degradation in the Middle Citarum Sub-Watershed, Indonesia - Ambarwulan, Wiwin; Nahib, Irmadi; Widiatmaka, Widiatmaka; Suryanta, Jaka; Munajati, Sri Lestari; Suwarno, Yatin; Turmudi, Turmudi; Darmawan, Mulyanto; Sutrisno, Dewayany (Frontiers in Environmental Science, 2021)
Land degradation (LD) is an important issue worldwide because it affects food production and people’s welfare. Many factors cause land degradation, but in humid tropical areas, erosion is the main factor. More than 100 countries including Indonesia are affected by LD. Watershed management should be prioritized owing to budget constraints, while on the other side, the area affected by LD is very large compared to the size of the existing land area. The Middle Citarum Sub-Watershed (MCSW) is one of the most degraded drylands in Indonesia where the environment can be considered a typical humid tropical watershed. The objective of this study was to map degraded lands and prioritize restoration using a combined approach of the Universal Soil Loss Equation (USLE). the analytical hierarchy process (AHP) and geographic information systems (GIS) in a multicriteria decision analysis (MCDA) environment. The severity of LD was estimated quantitatively by analyzing the parameters of land use and land cover, slope, soil erosion, productivity, and management. The results indicated that the MCSW is dominated by the potentially degraded land classes (38%), followed by the degraded land classes (21%). The prioritization of LD restoration is suggested in the area of very high and high degraded land. The method developed in this research work could be adopted as a tool to guide decision makers toward sustainable land resource management in humid tropical watersheds affected by LD.